BN Heterosuperbenzenes: Synthesis and Properties - Wang, Xiao-Ye; Wang, Jie-Yu; Pei, Jian (Chemistry : a European journal, 2015)
Replacement of CC unit with its isoelectronic BN unit in aromatics provides a new class of molecules with appealing properties, which have attracted great attention recently. In this Concept, we focus on BN‐substituted polycyclic aromatics with fused structures, and review their synthesis, photophysical, and redox properties, as well as their applications in organic electronics. We also present challenging synthetic targets, large BN‐ substituted polycyclic aromatics, such as regioregular BN heterosuperbenzenes, which can be viewed as BN‐doped nanographenes. Finally, we propose an atomically precise bottom‐up synthesis of structurally well‐defined BN‐doped graphenes. A new super hero! BN substitution in aromatic systems could provide a new family of interesting compounds. In this Concept, the development of BN‐substituted polycyclic aromatics is reported, and their synthesis, properties and electronic applications are summarized. From monocyclic BN‐substituted benzene to polycyclic BN heteroaromatics (like BN heterosuperbenzene), the possible ways to structurally well‐defined BN‐doped graphenes are proposed.